Covalent functionalization of graphene with 1, 5-diaminonaphthalene and ultrasmall palladium nanoparticles for electrocatalytic oxygen reduction. (26th January 2017) - Park, Dongchul; Ahmed, Mohammad Shamsuddin; Jeon, Seungwon
Abstract: 1, 5-diaminonaphthalene and ultrasmall palladium nanoparticles (PdNPs) embedded electrochemically reduced graphene oxide (denoted as ERGO-DAN-Pd) was successfully synthesized and employed as a cathode catalyst for enhanced oxygen reduction reaction (ORR) in direct alkaline fuel cells (DAFCs). The physical properties of ERGO-DAN-Pd were investigated using several instrumental methods. The morphological characterizations demonstrate that the ultrasmall PdNPs were homogeneously dispersed on the ERGO-DAN film. X-ray analysis confirmed the successful covalent functionalization of graphene sheets with DAN. The electrocatalytic activity of ERGO-DAN-Pd towards ORR was excellent compared to other electrodes in 0.1 M KOH electrolyte. Particularly, it showed 1.8 and 2.7 magnitude higher mass activity with large specific activity compared to 20 wt.% Pt/C and nonfunctionalized ERGO/Pd, respectively. Moreover, the reaction kinetic parameters confirmed that the ORR at ERGO-DAN-Pd catalyst was followed by a 4e − process with faster electron transfer rate per O2 with better stability and fuel selectivity than state-of-the-are Pt/C for DAFCs application. Graphical abstract: Highlights: 1, 5-diaminonaphthalene functionalized graphene with PdNPs was prepared, ERGO-DAN-Pd. Ultrasmall PdNPs were homogeneously dispersed on the ERGO-DAN film than ERGO film. It showed 1.8 and 2.7 times higher mass activity than Pt/C and DAN-free ERGO/Pd. It exhibited good stability and fuel selectivity in DAFCs that Pt/C during ORR.